ANALISIS SAHAM PT INDOSAT Tbk TERKAIT RENCANA BUY BACK PEMERINTAH - A Zaenal Abidin (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract.The study aims to analyze the value of buyback stock plan related to theacquisition of PT Indosat Tbk (ISAT). Counting reasonable price stock carried method Capital Asset Pricing Models (CAPM), Free Cash Flow to Equity (FCFE), Relative Valuation, and Gordon Growth Model. Under the CAPM method, FCFE, and Gordon Growth Model value of ISAT is undervalued. Based on Relative Valuation approach by comparison Telkom and XL Axiata ISAT values obtained is overvaluedKeyword: Acquisitions, Capital Asset Pricing Madels (CAPM), Free Cash Flow to Equity (FCFE), Relative Valuation, Gordon Growth Model, Undervalued, Overvalued